ROMEO: a rapid rule out strategy for low risk chest pain. Does it work in a UK emergency department?. Issue 5 (1st September 2002) - Taylor, C; Forrest-Hay, A; Meek, S
Abstract : Aims: To examine the feasibility of using the ROMEO (rule out myocardial events on "obs" ward) pathway for low risk patients with chest pain in a UK emergency department. Methods: A prospective study was undertaken to determine outcomes for the first 100 patients entering the pathway (from May to Oct 1999). Serum troponin levels, serial ECG recordings, exercise test result, total length of stay, and final diagnoses were reviewed. Patients were telephoned after discharge to inquire about persisting or recurrent pain, and further investigations after completing the ROMEO pathway. Results: 82 of 100 (82%) had myocardial damage excluded by serum troponin assay. Sixty two of 82 (76%) of these completed exercise tolerance testing (ETT). Fifty seven of 62 (92%) ETTs were negative. Twenty of 82 (26%) did not undergo ETT because of mobility problems, recent ETT, or if considered very low probability of cardiac pain on consultant review. Five of 100 (5%) had an increased initial troponin and five of 100 (5%) had an increased 12 hour troponin. These patients were referred for admission under the general physicians. Seven of 100 (7%) were referred for other reasons (late ECG changes, continuing or worsening pain). One patient self discharged. Length of stay varied because of changes to arrangements for ETT. The median time for all patients over the period studied was 23 hours. All patients were discharged within an hour of a negative ETT. Follow up results: 67 of 74 (91%) eligible patients were contacted by telephone. Forty six of 67 (69%) had no further pain, attendances, or GP consultations. Six of 67 (9%) had further cardiological investigation or treatment. Conclusions: A rapid rule out strategy such as the ROMEO pathway is feasible in the UK healthcare setting and provides standardised and consistent evaluation.